2012
DOI: 10.1128/cvi.00194-12
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C Virus Infection Breaks Tolerance and Drives Polyclonal Expansion of Autoreactive B Cells

Abstract: b Chronic Hepatitis C virus (HCV) infection has been linked with B cell lymphoproliferative disorders and several autoimmune-related diseases. The mechanisms of how chronic viral infection affects B cell development and predisposes the patients to autoimmune manifestations are poorly understood. In this study, we established an experimental system to probe the B cell responses and characterize the antibodies from chronic-HCV-infected individuals. We identified an unusual polyclonal expansion of the IgM memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…Consistent with a previous report (17), the present study demonstrated that an increase in CD27+IgM+B cells was associated with HCV infection. The frequency of CD27-IgM+B cells in patients with CHC was similar to that in HCs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with a previous report (17), the present study demonstrated that an increase in CD27+IgM+B cells was associated with HCV infection. The frequency of CD27-IgM+B cells in patients with CHC was similar to that in HCs.…”
Section: Discussionsupporting
confidence: 93%
“…Roughan et al (17) demonstrated that IgM+ memory B cells were expanded in patients with CHC, and identified that the unusual polyclonal expansion of the IgM+ memory B cell subset was made up of autoreactive B cells. Consistent with a previous report (17), the present study demonstrated that an increase in CD27+IgM+B cells was associated with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these B-cells in HCV-infected patients are autoreactive [68]; and, therefore, may predispose to SS.…”
Section: Hcvmentioning
confidence: 99%